Therapeutic Hypothermia Inhibits Hypoxia‐Induced Cardiomyocyte Apoptosis Via the MiR‐483‐3p/Cdk9 Axis - Qiqi Xue; Qianru Zhang; Zhenzhen Guo; Liping Wu; Yafen Chen; Zhongli Chen; Ke Yang; Jiumei Cao (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Therapeutic hypothermia has a beneficial effect on cardiac function after acute myocardial infarction, but the exact mechanism is still unclear. Recent research has suggested that microRNAs participate in acute myocardial infarction to regulate cardiomyocyte survival. This study aimed to explore the ability of hypothermia‐regulated microRNA‐483‐3p (miR‐483‐3p) to inhibit hypoxia‐induced myocardial infarction. Methods and Results Primary cardiomyocytes were cultured under hypoxia at 32 °C to mimic therapeutic hypothermia, and the differentially expressed microRNAs were determined by RNA sequencing. Therapeutic hypothermia recovered hypoxia‐induced increases in apoptosis, decreases in ATP levels, and decreases in miR‐483‐3p expression. Overexpression of miR‐483‐3p exhibited effects similar to those of therapeutic hypothermia on hypoxia in the treatment of cardiomyocytes to associate with maintaining the mitochondrial membrane potential, and cyclin‐dependent kinase 9 (Cdk9) was identified as a target gene with downregulated expression by miR‐483‐3p. Knockdown of Cdk9 also promoted cardiac survival, ATP production, and mitochondrial membrane potential stability under hypoxia. In vivo, the expression of miR‐483‐3p and Cdk9 was tested in the cardiac tissue of the mice with acute myocardial infarction, and the expression of miR‐483‐3p decreased and Cdk9 increased in the region of myocardial infarction. However, miR‐483‐3p was overexpressed with lentivirus, which suppressed apoptosis, infarct size (miR‐483‐3p, 22.00±4.04% versus negative control, 28.57±5.44%, P<0.05), and Cdk9 expression to improve cardiac contractility. Conclusions MiR‐483‐3p antagonizes hypoxia, leading to cardiomyocyte injury by targeting Cdk9, which is a new mechanism of therapeutic hypothermia.